RESPONS FUNGSIONAL LARVA Menochilus sexmaculatus TERHADAP KELIMPAHAN KUTU DAUN Aphis craccivora - Junianto S Batubara (Jurnal Education and Development, 2022)
Long beans are one of the strategic horticultural commodities in Indonesia. One of the important pests on long bean plants is the aphid Aphis craccivora Koch (Hemiptera: Aphididae). A. craccivora attacks long bean plants starting from the vegetative to generative phase. This research was conducted with the aim of knowing the functional response of the predator Menochilus Sexmaculatus to the increased control of aphids A. craccivora and the functional response parameters “a” and “Th” on M. Sexmaculatus. This research was conducted in Dramaga, Bogor Regency. Based on the observation that the increase in the density of A. craccivora, the predation rate of A. craccivora by predators of M. sexmaculatus also increased, resulting in an increase in the functional response of M. sexmaculatus.